Fintech, Blockchain, Islamic Finance: A Systematic Literature Review - Milla Febriza; Ahmad Wira; Aidil Novia (UIN Siber Syekh Nurjati Cirebon, 2025)
Introduction: The rapid development of financial technology (fintech) and blockchain has brought a major transformation in the global industry, including in the Islamic finance sector. However, integrating fintech and blockchain with Sharia principles remains a challenge and has not been studied systematically. This research aims to map and analyze the development of research related to Fintech, Blockchain, and Islamic finance, identifying trends, research gaps, and future development directions.Methods: This study employed a qualitative research method with a Systematic Literature Review approach, utilizing a model prism. The data source for this study consisted of published articles obtained from Scopus and Emerald. The study's results showed that 30 articles, published in Scopus and Emerald, were published between 2015 and 2024. Results: Based on the findings obtained, it is evident that blockchain technology, fintech, and digital innovation have significant potential in enhancing the efficiency, transparency, and inclusivity of Islamic finance, particularly through applications in zakat, waqf, sukuk, and crowdfunding. Despite regulatory and collaboration challenges, these technologies have been able to eradicate poverty, support economic development, and expand access to finance, including in non-Muslim countries. Technology adoption is also influenced by religiosity factors and perception of benefits, confirming the need for global regulatory and standard support to maximize its benefits. Conclusion and Suggestion: The reviewed studies suggest that blockchain technology has significant potential to strengthen trust and compliance with Shariah by enabling smart contracts, decentralized financial products, and transparent auditing mechanisms. Moreover, fintech solutions can expand financial inclusion in Muslim-majority countries and beyond, especially for the unbanked population. However, challenges remain in terms of regulatory frameworks, Shariah standardization, scalability of blockchain applications, and the readiness of financial institutions and customers to adopt these innovations. In conclusion, while fintech and blockchain present strong prospects for advancing Islamic finance, further research and practical implementation are required to fully realize their potential in providing Shariah-compliant, inclusive, and sustainable financial services.